Experimental testing on plastic hinge formation on steel beams : deflection and rotation angle profiles - Jacky Poea (2012)
In this project, study on the formation of plastic hinge including the spread of plastic zone and the length of the plastic hinge, the deflection and rotation angle profiles are carried out by experimental testing on Laboratory and finite element (FE) modelling using the general purpose FE software, ABAQUS. Six RHS steel beams (three specimens of 75mm x 50mm x 6mm and three specimens of 50mm x 75mm x 6mm) are tested with the propped cantilever support condition. An incremental single point load will be applied to the mid span of each test. Instrumentation such as strain gauges, LVDTs, digital camera, graph paper, etc. are installed to capture all the relevant data.